Development and validation of a low-cost polymer selective laser sintering machine. (October 2020) - Mapley, Martin; Lu, Yidi; Gregory, Shaun D.; Pauls, Jo P.; Tansley, Geoff; Busch, Andrew
Graphical abstract: Abstract: Due to manufacturer implemented processing parameter restrictions and the cost prohibitive nature of selective laser sintering (SLS) machines, researchers have limited opportunities to explore the processing of new materials using this additive manufacturing (3D printing) process. Accordingly, this article aimed to overcome these limitations by describing the build and operation of a customizable low-cost polymer SLS machine. The machine boasts a three piston powder bed with the center build piston heated by PID controlled ceramic heaters. Thermal energy for powder consolidation was provided via a 2.44 W solid state diode laser which was mechanically traversed using stepper motor driven belt drives. New layers of powder were deposited by a counter-rotating roller system. The SLS machine was controlled by executing G-code in Mach3 allowing full customization of processing parameters. The machine demonstrated the production of parts from polyamide-12 reaching densities of 918 ± 9 kg/m 3 while achieving an elastic modulus of 358.36 ± 3.04 MPa and elongation at break of 11.13 ± 0.02%. With part properties similar to those achievable with a commercial machine, this low-cost SLS machine could be a vital tool in assisting researchers to explore the processing of new materials.